Is Corporate Tax Avoidance Associated with Investment Efficiency? - Asiri, Mohammed; Al-Hadi, Ahmed; Taylor, Grantley; Duong, Lien (2020)
The purpose of this study is to examine the association between investment efficiency and corporate tax avoidance. Using a large sample of U.S. firms over the period 1993–2016, we show that there is a positive association between corporate tax avoidance activities and investment inefficiency. Moreover, we find that the association is mediated by financial statement readability, financial statement comparability and product market competition. Our results are robust to alternative measures of both tax avoidance and investment inefficiency. Propensity score matching (PSM), difference-in-difference (DID), and two-stage least squares (2SLS) regression analyses confirm our results and mitigate any potential endogeneity issues that might result from the effect of omitted variables, reverse causality or model misspecification.